The Past Is Still With Us: Slavery and Social Conflict in Twenty-First Century Igboland, Nigeria - Opata , Christian Chukwuma; Apeh, Apex A; Amaechi, Chidi (University of Nigeria Journal of Political Economy, 2022)
Scholarly accounts of slavery and its associated trade indicate that the Igbo were major players either as slave merchants, articles of the trade or slave keepers. During the inglorious days of slavery, there were several accounts among the Igbo indicating that they never took kindly to being regarded and treated as slaves. However, even after the abolition and subsequent legislations in support of abolition in eastern Nigeria to which the Igbo belong, the old notion of slavery and the practices associated with the institution refused to fizzle away. Consequent on the entrenched notions about slavery, many Igbo communities even in the present century are enmeshed in antagonistic relations between those assumed to be of slave ancestry and those not of slave descent. That such crisis exists even in the face of law raises serious concerns albeit; what is the bone of contention among the opposing parties in such crisis–ridden communities and how could they be resolved? This article which is a result of extensive field investigation is intended to provide answers to the questions using specific examples from some Igbo communities with a view to recommending ways of minimising the rancour and acrimony among the groups (ex-slaves and non-slaves).